Behavior of tube-reinforced double-layer honeycomb sandwich structure subjected to low-velocity impact. Issue 2 (17th January 2023) - Yan, Leilei; Zhang, Yunwei; Zhu, Keyu; Zhang, Chun
Abstract: To improve the load carrying capacity, structural stiffness, and impact resistance of honeycomb sandwich structure, a novel tube-reinforced double-layer honeycomb sandwich structure was proposed by filling metallic tubes on the honeycomb holes. The low-velocity impact test was carried out on the tube-reinforced structure experimentally and numerically to evaluate its low-velocity impact response. It indicated that the stiffness, first linear stage slopes, and impact resistance of the honeycomb sandwich structure were increased by tube filling. Besides, the stress and deformation distribution of front and back panels were changed into more scattered and uniform, resulting in the reduction of maximum deflection. The maximum deflection of the front panel could be effectively reduced by filling the upper honeycomb core with aluminum tubes. Filling the lower honeycomb core with aluminum tubes could greatly reduce the maximum deflection of the middle and rear panels. The tube-reinforced honeycomb sandwich structure was a promising structure for weight sensitive applications owing to its improved load carrying capacity and impact resistance.